A new blind snake of the genus Letheobia (Serpentes: Typhlopidae) from Rwanda with redescriptions of L. gracilis (Sternfeld, 1910) and L. graueri (Sternfeld, 1912) and the introduction of a non-invasive preparation procedure for scanning electron microscopy in zoology - Dehling, J. Maximilian; Hinkel, Harald H.; Ensikat, Hans-Jürgen; Babilon, Kenny; Fischer, Eberhard (Zootaxa, 2018)
A new species of blind snake in the genus Letheobia is described from Akagera National Park in eastern Rwanda. The new species is most similar to species of the L. gracilis complex, particularly L. gracilis and L. graueri. It differs from all other species of the genus by a unique combination of morphological characters, including the highest number of middorsal scale rows (834) and the most extreme elongation (total-length/midbody-width ratio 131) of all species in the genus and of any species of snake in the world; 22-22-22 longitudinal scale rows; snout in dorsal profile rounded, in lateral profile bluntly rounded with an angular horizontal edge ventrally; rostral broad, posteriorly rounded; eyes invisible; supralabial imbrication pattern T-0; tail short (1.3 percent of total length) with an apical spine; and a pink life colouration. The holotype of the new species was collected in gallery forest at a lake shore surrounded by savanna at 1300 m elevation. We produced scanning electron microscope images of the heads of the investigated specimens applying a liquid-substitution preparation procedure which does not require coating or drying and thus does not irreversibly damage the investigated samples. The obtained images allow an easy and more accurate examination of the scalation.